Local landscape units in the northeast of Michoacán, México - López-Navarro, Alexis (2018)
The objective was to prepare a map of landscape units combining an expert and local approach, for the planning of the territory in the Northeast of the State of Michoacán. The expert approach used the methodology of physical-geographical landscapes, obtaining landscape units, which were interpreted by local actors, through the application of participatory tools; where semi-structured interviews were applied, transects in the field; mental maps were made, and Geographical Information Systems were used. It was found that both approaches have contrasting differences. On the one hand, the expert approach defines the units of landscapes by biophysical features; instead, people through the knowledge they have, recognize the attributes and delimit the landscape units, by the land uses that they give them. It is concluded that it is important to use hybrid methods to study community practices in the management of common use resources.